Macroeconomic Prospects of the Philippines in 2022–2023: Steering through Global Headwinds - Margarita Debuque-Gonzales; John Paul P. Corpus; Ramona Maria L. Miral (Philippine Institute for Development Studies (PIDS), 2022)
This paper, which will be released as the lead chapter of the 2021-2022 PIDS Economic Policy Monitor, reviews the Philippines' macroeconomic performance in 2021 and the first half of 2022, analyzes recent developments and challenges shaping the economy's near-term outlook, and presents macroeconomic projections for 2022 and 2023. With the country's sustained economic reopening, the analysis suggests that GDP growth may grow by about 7.1 percent, but economic activity may weaken in 2023 as the global economic environment deteriorates. Inflation will likely continue to be elevated in 2022 but may still fall within the central bank's target range in 2023. The economic outlook features significant challenges and downside risks, including persistently high inflation, an uncertain business environment, and a possible downturn in the world's major economies. The paper ends by outlining what the authors believe should count among government's key priorities in steering the economy through these headwinds.
Keywords: 330; Philippine economy; growth; inflation; forecast